2005
DOI: 10.1590/s0100-41582005000600007
|View full text |Cite
|
Sign up to set email alerts
|

Resistência de cultivares e linhagens de tomateiro a Tomato chlorotic spot virus e a Potato virus Y

Abstract: Linhagens avançadas do programa de melhoramento do tomateiro (Lycopersicon esculentum) do IAC foram avaliadas em condições de campo em Campinas (SP) para resistência a tospovírus e a potyvírus, nos anos agrícolas 2002/2003 e 2003/2004, respectivamente. No primeiro ano, a única espécie de tospovírus que ocorreu na área experimental foi Tomato chlorotic spot virus (TCSV). As sete linhagens do grupo IAC exibiram baixa porcentagem de plantas sintomáticas em duas avaliações, com médias abaixo de 28%; as cultivares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
3
0
3
Order By: Relevance
“…Lourenção et al (2005) ressaltaram ainda a importância que os condimentos também podem assumir na contaminação final quando utilizados em produtos do tipo frescal. Nas amostras de pimenta-do-reino e orégano analisadas por esses autores, 36,4% e 6,1%, respectivamente, estavam em desacordo com a legislação nacional vigente.…”
Section: Resultsunclassified
“…Lourenção et al (2005) ressaltaram ainda a importância que os condimentos também podem assumir na contaminação final quando utilizados em produtos do tipo frescal. Nas amostras de pimenta-do-reino e orégano analisadas por esses autores, 36,4% e 6,1%, respectivamente, estavam em desacordo com a legislação nacional vigente.…”
Section: Resultsunclassified
“…Contrary to what is found in Capsicum, in which resistance sources have already been identified in C. annuum, in commercial terms the most important species in the genus, C. chinense, and now in C. baccatum, in tomato, Juhász et al (2006) did not find resistance among the 355 Lycopersicon esculentum accessions studied and, among 21 wild relatives, only a single accession of L. hirsutum was resistant. Lourenção et al (2005) identified only two sources of resistance to Potyvirus in tomato when assessing 16 tomato genotypes. On the other hand, in Capsicum, Nascimento et al (2007), found resistance to the PepYMV in six experimental and one commercial hybrids out of 26 genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…The LA 444‐1 accession was also resistant to the tospovirus Tomato spotted wilt virus (TSWV) in field exposure tests over seven consecutive years (Lourenção et al ., ). In addition, the accession LA 444‐1 showed a high level of resistance to the begomovirus Tomato yellow vein streak virus (TYVSV) (Matos et al ., ), and the potyvirus Potato virus Y , strain PVY O (Lourenção et al ., ). Taking all these data together and considering the low genetic diversity of the ToCV Brazilian isolates based on the partial nucleotide sequence of the Hsp70h homologous gene (Barbosa et al ., ), as well as the high degree of nucleotide identity with isolates from other countries (Albuquerque et al ., ), it is believed that the lineage IAC‐CN‐RT might be of great value for tomato breeding programmes.…”
Section: Discussionmentioning
confidence: 97%